2022
DOI: 10.3889/oamjms.2022.9300
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Androgen Receptor Expression in Prostate Adenocarcinoma

Abstract: Prostate cancer is one of the most common cancer worldwide, where South Sulawesi is included in four provinces with the highest prevalence of prostate cancer in Indonesia. Laboratorium Sentra Patologia Makassar (SDPM) stated that prostate cancer cases continue to rise each year. Androgen receptor (AR) plays a role in the growth and differentiation of male urogenital structures, both under normal and neoplastic conditions, the neoplastic condition is caused by the mechanism of the AR pathway which undergoes cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
3
0
0
Order By: Relevance
“…85.3%± 9.7%, P < 0.001). Similar results were obtained by Putriyuni and Oktora (20) who found low AR expression in 48,21% (27 cases) while high AR expression was seen in 51,79% (29 cases), Henshall et al (21) who found overexpression of AR (≥70% positive nuclei) in the malignant epithelium and loss of AR immunoreactivity in the adjacent periepithelial stroma (≤30%) and Osman et al (16) who found that mean value of AR expression was significantly higher in prostatic carcinomas than in benign hyperplasia (P = 0.001). That didn't agree with Segawa et al (22) who found that the expression of AR in the tumor cells (52.2 ± 27.1%) was significantly lower than that in the non-tumorous tissue (68.3 ± 8.3%; P < 0.001).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…85.3%± 9.7%, P < 0.001). Similar results were obtained by Putriyuni and Oktora (20) who found low AR expression in 48,21% (27 cases) while high AR expression was seen in 51,79% (29 cases), Henshall et al (21) who found overexpression of AR (≥70% positive nuclei) in the malignant epithelium and loss of AR immunoreactivity in the adjacent periepithelial stroma (≤30%) and Osman et al (16) who found that mean value of AR expression was significantly higher in prostatic carcinomas than in benign hyperplasia (P = 0.001). That didn't agree with Segawa et al (22) who found that the expression of AR in the tumor cells (52.2 ± 27.1%) was significantly lower than that in the non-tumorous tissue (68.3 ± 8.3%; P < 0.001).…”
Section: Discussionsupporting
confidence: 91%
“…In our study, there was a statistically significant association between high AR expression and higher Total Gleason score (p value=0.008) with AR-positive specimens (with a mean of 7.67) having higher total Gleason score than AR negative ones (with a mean of 6.40) & statistically significant difference between different grade groups regarding AR expression (P value =0.001). These results are in keeping with Putriyuni and Oktora (20) who reported a Significant correlation of AR expression with the Gleason score (p=0.018) . It indicated that prostate cancer with a high-grade Gleason score had 5,098 times high AR expression rather than low AR expression and Hashmi et al (19) found a Significant association of AR expression with total Gleason score, WHO grade, and percentage of tissue involvement (tumor quantification) which are among the most important markers of tumor progression.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation